Redefining Immediacy for Email Satisfactory Communication: South-East Nigerian Lecturers Perspectives - Anumudu, Chinedu Eugenia; Yasin, Megat Al-Imran; Ghazali, Akmar Ahmad; Alsagoff, Syed Agil (Jurnal The Messenger, 2020)
Notwithstanding the empirical evidence that Nigerian academic staff utilized email as one of asynchronous virtual communications, recent studies pointed that low productivities were still witnessed by them due to email inability of giving them timely responses as viable means of communication. Therefore, this study was necessitated for redefining immediacy effects towards reaching email satisfactory communication among South-East Nigerian academic staff. Qualitative investigative study via case study was conducted towards soliciting their views on how to redefine immediacy for email satisfactory communication. The major findings of the study demonstrated that effective internet availability and affordable subscriptions, homophilous patterns of communications, content structure strategy, enhancing regularly email checking awareness, and power supply availability were the immediate remedies for achieving email satisfactory communication. The study eventually recommended that these factors should be taken into considerations by them towards attaining email satisfactory communication and in other asynchronous virtual communication mediums.
Keywords: Redefining Immediacy; Email; Satisfactory Communication; South-East Nigerian Academic Staff